Innovation in the Lubusz region. Implementation of an innovation management system - Malon, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article reveals the potential of innovation management in regions on the example of the Lubusz Voivodeship. The aim of the article is to analyse the latest activities and initiatives supporting innovation in the Lubusz Voivodeship. To this end, it was important to identify the nature of the implementation process of innovative solutions, which may be recognised as political, i.e.: characterised by top-down initiatives and bottom-up implementation.
Keywords: education; innovation; innovation management; development of enterprises; learning regions